2019
DOI: 10.1111/cen.14122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clomiphene citrate treatment on the Sertoli cells of dysmetabolic obese men with low testosterone levels

Abstract: Background: Clomiphene citrate (CC) has been shown to restore the hypothalamicpituitary-gonadal (HPG) axis by increasing testosterone (T) levels to physiological levels in patients with dysmetabolic conditions such as obesity, metabolic syndrome and type 2 diabetes mellitus (T2DM). However, the data are unclear regarding the effects on Sertoli cell (SC) function. Aim:To study SC function by assessing Inhibin B (IB) and anti-Mullerian hormone (AMH) levels at baseline and after 3 months of CC treatment. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…A similar mechanism would also explain the increased values of E and 17OH-P4. These data are in line with few studies on the CC effect on CBG which showed an increase in the protein related to the treatment through an estrogen-like effect [10,38]. However, we cannot completely rule out a synthesis by the adrenal gland, as apparently suggested by the CYP11B1 expression (F/11 S), nor a reduction in the oxidative metabolism at the target tissues, as suggested by the reduced 11βHDS2 activity (F/E).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A similar mechanism would also explain the increased values of E and 17OH-P4. These data are in line with few studies on the CC effect on CBG which showed an increase in the protein related to the treatment through an estrogen-like effect [10,38]. However, we cannot completely rule out a synthesis by the adrenal gland, as apparently suggested by the CYP11B1 expression (F/11 S), nor a reduction in the oxidative metabolism at the target tissues, as suggested by the reduced 11βHDS2 activity (F/E).…”
Section: Discussionsupporting
confidence: 80%
“…In our previous studies we showed that, besides T, CC therapy results in increasing serum DHT, E2, the sex hormones binding globulin (SHBG), LH, and FSH [5,38]. In the present study, we added the novel finding that CC administration along with Met significantly increases circulating E1, 17αOH-P4, F, E, and CBG, but not other steroids including androgen and glucocorticoid precursors, such as 17αOH-P5, A, DHEA, and 11 S levels (see ▶Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, we found increased levels of FSH in CUFA individuals, though no significant increase in FSH levels was observed in CUFA rats, indicating that CUFA individuals might have a dysfunctional condition of Sertoli cells and, as a consequence, a hypothetical impairment of spermatogenesis. 35 Further semen analysis is still required to test fertility.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 To the best of our knowledge, only one research team investigated levels of this hormone in metformintreated men. Pelusi et al 41 observed that post-treatment concentrations of anti-Müllerian hormone did not differ between dysmetabolic obese men with low testosterone levels randomized to either metformin plus clomiphene citrate or to metformin plus placebo. In the current study, the impact of discontinuation of testosterone treatment differed, depending on whether patients received metformin treatment.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%